Case Report: Asuhan Kebidanan Komprehensif Pada Ny. M di Kota Langsa - Magfirah Magfirah; Idwar Idwar (Malahayati Nursing Journal, 2025)
ABSTRACT Continuity of Care is a continuous service starting from pregnancy, childbirth, postpartum, newborn care (BBL), and family planning (KB) services. The research design is descriptive, and the type of research is a case study. Continuous midwifery care was provided to Mrs. M. Data collection techniques Data collection includes observation, physical examination, and documentation. Comprehensive midwifery care was provided to Mrs. M, G2P1A0, aged 25 years. Midwifery care during the third trimester of pregnancy with complaints of back pain, so care provided included a gym ball and warm compresses. The mother also felt tired and difficulty sleeping, so care included lavender aromatherapy and date juice. During the first stage of labor, the mother felt anxious, so she listened to the recitation of the Quran and received Effleurage Massage. During the second stage of labor, the mother pushed effectively, and the baby was born spontaneously weighing 3500 grams, crying, with active movements and a pink skin color. The umbilical cord was delayed in cutting for 2 minutes, followed by Early Breastfeeding Initiation (EBI). cord clamping for 2 minutes followed by Early Breastfeeding Initiation (EBI). Neonatal care included eye ointment, vitamin K, and HB 0. During the 6-hour postpartum care, breastfeeding techniques were taught, and education on the benefits of sweet potato leaves to increase breast milk production was provided. On the fourth postpartum visit, Mrs. M complained of perineal wound pain; care provided included education on the benefits of boiled betel leaf water. Mrs. M's baby had heat rash (Miliriasis), so Virgin Coconut Oil (VCO) was provided, along with a booklet on early detection of childhood diseases. On the 14th postpartum visit, instructions were given on store breast milk and recommended that the baby receive the BCG vaccination. Family planning care for Mrs. M used the Lactational Amenorrhea Method (LAM). After completing LAM, Mrs. M continued with the mini-pill. Comprehensive midwifery care for Mrs. M was conducted Keywords: Care, Comprehensive, Evidence-Based Midwifery.    ABSTRAK Continuity of Care merupakan pelayanan yang berkelanjutan mulai dari kehamilan, persalinan, nifas, pelayanan Bayi Baru Lahir (BBL) serta pelayanan Keluarga Berencana (KB). Desain penelitian deskriptif dan jenis penelitian Studi Kasus. Asuhan kebidanan secara berkesinambungan pada Ny.M. Tehnik pengumpulan data meliputi observasi, pemeriksaan fisik dan dokumentasi. Asuhan kebidanan komprensif diberikan pada Ny. M G2P1A0 usia 25 tahun. Asuhan Kebidanan kehamilan trimester III dengan keluhan nyeri punggung sehingga asuhan yang diberikan Gymball dan kompres hangat. Ibu juga merasa lelah dan sulit tidur asuhan diberikan Aromaterapi Lavender dan jus kurma. Asuhan Kebidanan persalinan kala I pase aktif ibu merasa cemas, ibu mendengarkan murotal Al Quran dan dilakukan Effluarege Massage. Kala II persalinan ibu mengedan dengan baik, bayi lahir spontan dengan berat 3500 gram, menangis, gerakan aktif, warna kulit kemerahan. Dilakukan penundaan pemotongan tali pusat selama 2 menit dilanjutkan Inisiasi Menyusu Dini (IMD).       Asuhan BBL diberikan salep mata, vitamin K dan HB 0. Pada asuhan nifas 6 jam, diajarkan tehnik menyusui, edukasi manfaat daun ubi jalar meningkatkan produksi ASI. Kunjungan nifas hari keempat Ny.M mengeluh nyeri luka perineum, asuhan yang diberikan edukasi manfaat air rebusan daun sirih. Bayi Ny. M mengalami biang keringat (Miliriasis) sehingga diberikan Virgin Coconut Oil (VCO) dan memberikan booklet tentang deteksi dini penyakit anak. Kunjungan nifas hari ke empat belas postpartum mengajarkan cara menyimpan ASI dan menganjurkan agar bayi diberikan imunisasi BCG. Asuhan KB pada Ny.M menggunakan Metode Amenore Laktasi (MAL). Setelah selesai MAL Ny.M dilanjutkan dengan mini pil. Asuhan kebidanan Komprehensif pada Ny. M dilaksanakan berdasarkan Evidence Based Midwifery. Kata Kunci: Asuhan, Komprehensif, Evidence-Based Midwifery.